2011
DOI: 10.1007/s00455-011-9360-2
|View full text |Cite
|
Sign up to set email alerts
|

Does PEG Use Cause Dysphagia in Head and Neck Cancer Patients?

Abstract: Percutaneous endoscopic gastrostomy (PEG) use is common in patients who undergo radiotherapy (RT) for head and neck cancer to maintain weight and nutrition during treatment. However, the true effect of PEG use on weight maintenance and its potential impact on long-term dysphagia outcomes have not been adequately studied. This retrospective study looked at swallowing-related outcomes among patients who received prophylactic PEG vs. those who did not, and among patients who maintained oral diets vs. partial oral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
113
1
4

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(124 citation statements)
references
References 15 publications
6
113
1
4
Order By: Relevance
“…One explanation for this discrepancy is that in some patients the weight loss is caused of decreased caloric intake, while in others weight loss is a manifestation of cachexia, or a syndrome of dysregulated catabolism and anabolism [17]. Historically, high-risk patients would have a percutaneous endoscopic gastrostomy (PEG) placed prior to starting treatment in order to prevent decreased caloric intake, but more recently there has been movement away from using feeding tubes due to concerns about delayed recovery of swallowing post-CTRT [18][19][20]. Interestingly, the placement of a PEG, or increased caloric intake alone, does not alleviate all the weight loss experienced during CTRT [12,19,21].…”
Section: Main Textmentioning
confidence: 99%
“…One explanation for this discrepancy is that in some patients the weight loss is caused of decreased caloric intake, while in others weight loss is a manifestation of cachexia, or a syndrome of dysregulated catabolism and anabolism [17]. Historically, high-risk patients would have a percutaneous endoscopic gastrostomy (PEG) placed prior to starting treatment in order to prevent decreased caloric intake, but more recently there has been movement away from using feeding tubes due to concerns about delayed recovery of swallowing post-CTRT [18][19][20]. Interestingly, the placement of a PEG, or increased caloric intake alone, does not alleviate all the weight loss experienced during CTRT [12,19,21].…”
Section: Main Textmentioning
confidence: 99%
“…Preventive rehabilitation programs have been associated with a long list of positive effects: improved QoL [20], better base of tongue retraction and better maintained epiglottic inversion [21], superior muscle maintenance and functional swallowing ability [22], better oral intake and clinician-rated swallowing function at three and 6 months [23], reduced extent and severity of penetration and/or aspiration, less trismus, less weight loss, and less pain (both short term [24] and at oneand two-years post-treatment [25]), and better oral intake and shorter duration of feeding tube dependency [26] posttreatment. Also maintained oral intake (no feeding tube dependency) has been shown to lead to better swallowing function after CCRT, possibly due to continued use of the swallowing musculature [26][27][28]. Benefits from preventive (swallowing) exercises have been reported in particular on the short term (up to 2 years) [19].…”
Section: Introductionmentioning
confidence: 96%
“…There are concerns in the literature that gastrostomy insertion can lead to dysphagia and tube dependency (Chen et al, 2010;Corry et al, 2008;Langmore et al, 2012;Mekhail et al, 2001), although other studies have shown no detrimental impact on swallowing function (Crombie et al, 2015;Silander et al, 2010) and the body of literature remains inconclusive from a recent systematic review (Shaw et al, 2015). Whilst the data from this current study suggests there may have been more tendency for the intervention group to use the tube for supplementary feeding for longer, with an increased use at four months post-treatment, there were no other statistical differences at any other time point.…”
Section: Gastrostomy Outcomes At 12 Monthsmentioning
confidence: 99%
“…Prophylactic gastrostomy tube (PGT) placement is a common method of nutrition support in patients with mucosal head and neck cancer (HNSCC), however there are concerns this leads to dysphagia and long term tube dependency (Chen et al, 2010;Corry et al, 2008;Langmore et al, 2012;Mekhail et al, 2001). Some studies have reported nil impact on swallowing function (Crombie et al, 2015;Silander et al, 2010), and the most recent systematic review on this topic remains inconclusive (Shaw et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation